Antioxidant and Antimicrobial Activity of Ferulago trojana E. Akalin & Pimenov - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2018)
Ferulago W. Koch is a genus in the Apiaceae family comprising 34 species, of which 18 are endemic in Turkey. Ferulago species have been known since the time of Dioscorides and have been used in folk medicine for their sedative, tonic, digestive, carminative, and aphrodisiac effects, as well as for the treatment of intestinal worms and hemorrhoids. This study was conducted to evaluate the polyphenolic contents and antioxidant activities of methanol extracts of the aerial parts (HFT) and rhizomes (RFT) of Ferulago trojana E. Akalin & Pimenov by measuring their ability to inhibit lipid peroxidation induced by Fe3+-ascorbate, their DPPH center dot and ABTS(center dot+) scavenging activities, and their ferric reducing antioxidant power (FRAP value). The methanol extracts were also examined for their antimicrobial activity using the microbroth dilution technique. Results showed that the methanol extracts of the aerial parts of the plant, containing the highest amount of total phenolic content and flavonoids, exhibited antioxidative potential for the chain-breaking inhibition of lipid peroxidation and showed the strongest hydrogen and single electron donor activities, which could thus serve as a free radical scavenger, act as a reductant, and provide protection against oxidative stress. Although the methanol extract of rhizomes did not exhibit any inhibitory effect on lipid peroxidation, it is possible that it might also have protective effects against oxidative damage by scavenging free radicals and acting as a reductant. While both the methanol extracts of the aerial parts and rhizomes of F. trojana were effective against Staphylococcus aureus, Methicillin-resistant S. aureus (MRSA), and S. epidermidis, the extracts showed no activity against Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. In addition, the methanol extract of rhizomes of F. trojana exhibited antibacterial activity against Proteus mirabilis and antifungal activity against the yeast Candida albicans.
Keywords: Ferulago; F. trojana; antioxidant activity; antimicrobial activity; ISAURICA PESMEN; WESTERN TURKEY; ESSENTIAL OIL; BOISS.; UMBELLIFERAE; FLAVONOIDS; EXTRACTS; ROOTS; ASSAY